Impact of Socio Economic Status on the level of job satisfaction of Women Workers in Hosiery units at Tiruppur - Saravanan, Dr. S. (Journal of Contemporary Research in Management (JCRM), 2013)
The role of women has been changing substantially over the last decade and a half, both inside and outside homes. In addition to their role within households, they are now having a larger role in the outside world also, especially in the labour market. It has often been argued that women face a segmented labour market with sector specific jobs and often gender specific wages assigned to them. However, the world is witnessing a significant change in this traditional thinking regarding ability of women to work only in a few specific sectors. More specifically, the present study is an empirical investigation into the identification of factors that determine the level of job satisfaction of female labour force working in the Hosiery Units of Tiruppur, Coimbatore on the basis of micro-level data. It tries to explain the level of job satisfaction of the female workers in terms of inter-linkages between socio economic status as measured by certain proxy factors like, the level of educational attainment, family background, employment status and job satisfaction.